2020
DOI: 10.1242/dmm.046920
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary neuroendocrine cells: physiology, tissue homeostasis and disease

Abstract: Mammalian lungs have the ability to recognize external environments by sensing different compounds in inhaled air. Pulmonary neuroendocrine cells (PNECs) are rare, multi-functional epithelial cells currently garnering attention as intrapulmonary sensors; PNECs can detect hypoxic conditions through chemoreception. Because PNEC overactivation has been reported in patients suffering from respiratory diseases – such as asthma, chronic obstructive pulmonary disease, bronchopulmonary dysplasia and other congenital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 138 publications
(206 reference statements)
1
54
0
Order By: Relevance
“…(See our review papers for more detailed information on the roles of Notch signaling 78 and neuroendocrine cells 79 in the mammalian respiratory system)…”
Section: Epithelial Developmentmentioning
confidence: 99%
“…(See our review papers for more detailed information on the roles of Notch signaling 78 and neuroendocrine cells 79 in the mammalian respiratory system)…”
Section: Epithelial Developmentmentioning
confidence: 99%
“…Studies using single-cell RNA-sequencing and numerous genetically engineered mouse models of specific lung cancer subtypes have suggested that distinct lung epithelial progenitor cells may undergo malignant transformation in lung cancer subtypes. For instance, neuroendocrine cells were shown to form SCLC tumor with Tp53 and Rb knockout (Leeman et al 2014;Song et al 2012;Noguchi et al 2020). Further, both BASC and ATII cells were demonstrated to contribute to Krasactivated ADC (Leeman et al 2014;Kim et al 2005;Xu et al 2012).…”
Section: Lung Cancermentioning
confidence: 99%
“…Pulmonary neuroendocrine cells are a small percentage (less than 1%) of pulmonary epithelial cells, innervated by the vagus nerve ( Noguchi et al, 2020 ). They sense oxygen through a NADPH oxidase coupled to a potassium channel sensitive to oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…They sense oxygen through a NADPH oxidase coupled to a potassium channel sensitive to oxygen. They may sense multiple chemical parameters from hypoxia to air pollutants in bronchial air (for example nicotine sensing through nicotinic Ach receptors), secrete serotonin, other peptides, and also ATP, which acts on autoreceptors and nerve terminals’ P2X receptors, and are involved in regulating Type 2 immune response ( Noguchi et al, 2020 ). They amplify allergic asthma responses ( Sui et al, 2018 ) via a neuroimmune mechanism ( Pavón-Romero et al, 2021 ), yet mitigate hypoxic injury ( Shivaraju et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%